2016
DOI: 10.14814/phy2.12684
|View full text |Cite
|
Sign up to set email alerts
|

Changes in corticospinal drive to spinal motoneurones following tablet-based practice of manual dexterity

Abstract: The use of touch screens, which require a high level of manual dexterity, has exploded since the development of smartphone and tablet technology. Manual dexterity relies on effective corticospinal control of finger muscles, and we therefore hypothesized that corticospinal drive to finger muscles can be optimized by tablet‐based motor practice. To investigate this, sixteen able‐bodied females practiced a tablet‐based game (3 × 10 min) with their nondominant hand requiring incrementally fast and precise pinching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 48 publications
2
16
1
Order By: Relevance
“…It may therefore be that the changes in performance that we observed are primarily related to recovery of muscle strength rather than improved muscle coordination. This would be consistent with the increase in MVC and it might also provide a possible explanation why we observed no change in CMC from T1 to T2, since changes in CMC have mainly been observed in other studies in relation to improvements in coordination (Larsen et al , 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It may therefore be that the changes in performance that we observed are primarily related to recovery of muscle strength rather than improved muscle coordination. This would be consistent with the increase in MVC and it might also provide a possible explanation why we observed no change in CMC from T1 to T2, since changes in CMC have mainly been observed in other studies in relation to improvements in coordination (Larsen et al , 2016).…”
Section: Discussionsupporting
confidence: 90%
“…motor training (Kristeva-Feige et al , 2002, Perez et al , 2006. Studies investigating CMC following a single bout of training in healthy participants have demonstrated that CMC is enhanced shortly after training and return to baseline within minutes despite maintained motor performance abilities (Perez et al , 2006, Geertsen et al , 2013, Larsen et al , 2016. Hence, we speculate that CMC may contribute to recovery by helping preserve and strengthen newly formed projections in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 86%
“…Periods of elevated beta synchrony have been associated with prolonged reaction time latencies (Gilbertson et al, 2005;Matsuya et al, 2013) and beta CMC reliably dissipates with movement. Reduced CMC might therefore result from ALS patients' disproportional need to mentally prepare for the upcoming movement, ostensibly in keeping with subjectively greater task difficulty since task practice has been shown to result in higher levels of beta CMC (Larsen et al, 2016). Relative CMC lateralisation in the ALS group might simultaneously have been compromised by dysfunction of interhemispheric communication (Karandreas et al, 2007).…”
Section: Activity-dependent Functional Connectivity In Alsmentioning
confidence: 99%
“…Another possible hypothesis indicates that PEF of the corticospinal system might be linked either to the higher level of arousal and changes in neurotransmitters induced by the exercise ( Tomporowski, 2003 ) or to feedback and feed-forward activation of sensory afferents and spinal neurons ( Jain et al, 2013 ; Ludyga et al, 2016 ). Therefore, it is likely that PEF of MEPs, postexercise cortical changes in β-band oscillations ( Witham and Baker, 2007 ) and corticomuscular coherence ( Larsen et al, 2016 ) represent temporary corticospinal plastic changes that have positive effects on subsequent task performance. Based on previous work it is conceivable that the higher attentional demands of a DT would have negative effect of exercise-induced sensorymotor plasticity ( Rosenkranz and Rothwell, 2006 ).…”
Section: Discussionmentioning
confidence: 99%